Business intelligence analytics: a proposal to measure the capability of an organization to transform data into value - Tourinho, Ana Lucia de Queiroz (2017)
The massive growth in the amount of data that companies, organizations, and society have been compelled to deal with, reinforce the need for studies on Business Intelligence, Business Intelligence Analytics and Big data. This subject remains among business agenda of priorities and has become more and more relevant since data and information comprise the raw material from which business strategies are developed to compete in a more complex and fast world. Therefore, understanding how to better exploit the available data is today a matter of great importance, not only as a business issue but also as an academic research topic. Within this scenario, where the best use of data is sought, the present study aims at developing a scientific research that enables to measure the capability of an organization to transform data into business value. Although certain aspects of the theme Business Intelligence, Business Intelligence Analytics and Big data are already established between researchers, there is still a lack of understanding and consensus on which are the antecedents of a Business Intelligence Analytics construct (BIA), and how to combine variables to enforce a better use of data. In addition, although researchers have addressed success in BIA by different approaches, we have also identified a lack of studies proving its effectiveness. In this study, we are proposing an integrated conceptual model for Business Intelligence Analytics Capability (BIAC) with proper scales to test its effectiveness. Ultimately, the BIAC may later be applied by firms to assess their level of maturity in BIA.